Pengaruh model pembelajaran indeks card match berbantuan media educaplay untuk meningkatkan hasil belajar siswa kelas V SD Negeri 158 Palembang - Rita Amelia; Kiki Aryaningrum; Mega Kusuma Putri (COLLASE (Creative of Learning Students Elementary Education), 2026)
This study aims to determine the effect of the Index Card Match Learning Model assisted by Educaplay Media to Improve Learning Outcomes of Fifth Grade Students of SD Negeri 158 Palembang. In this study using a quantitative approach with experimental methods, using the pre-experimental type, with a pretest-posttest control group design. The population and sample amounted to 45 students, class V A as the control class and class V B as the experimental class. data collection techniques used by researchers in this study are test techniques, and documentation. Instrument Validation Techniques in this study are validity tests and reliability tests. While the Data Analysis Techniques in this study are normality test, homogeneity test, and hypothesis testing. Based on the results of the Independent Samples Test, the significance value (Sig. 2-tailed) obtained is 0.000, both when the variances are considered equal and unequal. Since this value is smaller than 0.05, it can be concluded that there is a significant difference between the average learning outcomes of the two groups. This means that the difference in student learning outcomes scores does not occur by chance, but there is indeed a real influence from the treatment given to each group. This shows that the treatment applied has an effect on significantly improving student learning outcomes. In addition, the 95% confidence range also supports this conclusion because it does not pass zero, so the results of this test can be trusted. It can be concluded that there is an effect of the Index Card Match Learning Model assisted by Educaplay Media to Improve Learning Outcomes of Grade V Students of SD Negeri 158 Palembang